(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The evolution of management as a discipline has been driven by attempts to rationalize organizational performance and enhance human productivity. Two foundational paradigms—Scientific Management and Administrative Management—laid the intellectual framework for modern organizational studies. While both schools emerged during the industrial transformation of the late nineteenth and early twentieth centuries, they reflect different conceptual focal points: Scientific Management concentrates on the individual worker and task efficiency, whereas Administrative Management develops principles for structuring and coordinating the entire organization. This paper presents a comparative analysis of these schools, examining their origins, core assumptions, methodological principles, and long-term impact.